INVESTMENTS IN CONDITIONS OF DIVERSIFICATION OF UZBEKISTAN - Valiyev Babur Batirovich (Western European Studies, 2024)
This article is devoted to the analysis of current investment trends in the diversification of the national economy and the development of proposals to increase investment potential. The growth rate of investment in the regions of the country in recent years has been analyzed. Conclusions are drawn about the active attraction of investments.
Keywords: investments; diversification; national economy; territory